2018
DOI: 10.1007/s12072-018-9848-z
|View full text |Cite
|
Sign up to set email alerts
|

Long-term observation of acute-onset autoimmune hepatitis presenting clinically and radiologically as acute hepatitis

Abstract: Rapid progression of fibrosis could occur in A-AIH. Treatment response and long-term prognosis were good, and not different between patients with histologically acute and chronic hepatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Similar good treatment response and long‐term prognosis have been recently reported in a retrospective analysis of 30 Japanese patients with an acute but not severe form of the disease . Absence of ANA reactivity almost in half of our AS‐AIH patients is not a surprise as previous studies have shown that ANA and/or SMA could be negative in patients with acute AIH, a finding that might lead to delay of diagnosis .…”
Section: Discussionsupporting
confidence: 87%
“…Similar good treatment response and long‐term prognosis have been recently reported in a retrospective analysis of 30 Japanese patients with an acute but not severe form of the disease . Absence of ANA reactivity almost in half of our AS‐AIH patients is not a surprise as previous studies have shown that ANA and/or SMA could be negative in patients with acute AIH, a finding that might lead to delay of diagnosis .…”
Section: Discussionsupporting
confidence: 87%
“…The accumulation of findings of AIH with an acute presentation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and its novel diagnostic guidelines 22 may have affected the actual characteristics of AIH in Japan after the previous 2015 survey. The aim of this study was to elucidate the recent trends in AIH in Japan by comparing the results of the 2015 survey to a 2018 survey.…”
mentioning
confidence: 99%
“…Autoimmune hepatitis (AIH) is a poorly known immune-mediated autodestructive acute or chronic liver disease with female predominance and potential for the development of liver fibrosis [1][2][3][4][5][6][7][8]. AIH is characterized by elevated serum aminotransferase levels, the presence of hypergammaglobulinemia, circulating autoantibodies, and interface hepatitis with portal plasma cell lymphocytic necroinfiltration and rosetting of hepatocytes in histological examination [3][4][5][6][7][8][9][10][11]. Interface hepatitis in this pathology is closely related to the process of liver fibrosis [1,4,5,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…AIH is characterized by elevated serum aminotransferase levels, the presence of hypergammaglobulinemia, circulating autoantibodies, and interface hepatitis with portal plasma cell lymphocytic necroinfiltration and rosetting of hepatocytes in histological examination [3][4][5][6][7][8][9][10][11]. Interface hepatitis in this pathology is closely related to the process of liver fibrosis [1,4,5,[10][11][12][13]. It is a relatively rare but devastating disease, particularly aggressive in children/adolescents, leading in some cases to cirrhosis, liver failure, and death [5,7,10,[12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation